Expansion force induced in situ formation of a 3D boron nitride network for light-weight, low-k, low-loss, and thermally conductive composites. Issue 27 (30th June 2022) - Zhou, Shiqing; Xu, Yanting; Tang, Jiayue; Qian, Kaijing; Zhao, Jun; Wang, Jun; Gao, Hongwen; Li, Zhuo
Abstract : The expansion of thermally expandable microspheres forces the conductive fillers to segregate and form a 3D network in situ without any external assistance. Abstract : Building an interconnected filler network is the most effective way for polymer composites to attain a high thermal conductivity while minimizing the amount of fillers. However, previous approaches for network construction either have to be performed ex situ or rely on magnetic or electrical fields to achieve in situ formation, limiting their practical applications. Here we report a novel strategy to fabricate the filler network in situ without the assistance of any external fields. Thermally expandable microspheres (EMs) are added to the composite and their expansion at elevated temperature forces the conductive fillers to concentrate and align along the boundaries between adjacent microspheres, forming a continuous and densified 3D network. The obtained boron nitride nanosheet (BNNS)/EM/polydimethylsiloxane (PDMS) composite has a low density (0.55 g cm −3 ), low dielectric constant (<2.3), and excellent flexibility, while still exhibiting a high thermal conductivity of 0.94 W m −1 K −1 (9.82 vol% BNNS), which is 3.1 times that of randomly distributed ones. In addition, it has a low interface thermal resistance (20.93 mm 2 K W −1 ), only 1% of that of the assembled structure. These comprehensive properties make the composite ideal for thermal management of aerospace devices, high frequency electronic devices, and wearable electronics.